Taxonomic notes on Acanthopsis Harv. (Acanthaceae, tribe Acantheae): the group with trifid bracts - Steyn, Hester M.; Wyk, Abraham E. Van (Phytotaxa, 2017)
In the southern African genus Acanthopsis, the morphology of the bracts is taxonomically useful at the species level. This contribution focuses on the taxonomy and conservation status of those members of the genus characterized by inflorescences with trifid bracts, all of which are confined to arid parts of the Northern Cape Province, South Africa. Three species (A. dregeana, A. glauca and A. tetragona) and four subspecies are recognised in this group. One new species (A. tetragona) with two subspecies (A. tetragona subsp. tetragona and A. tetragona subsp. pedunculata) and one new subspecies (A. dregeana subsp. longispina) are described. Identification keys to the species and infraspecific taxa of the group with trifid bracts are provided.